Meningkatkan Kecerdasan Visual Spasial Pada Anak Usia Dini Melalui Permainan Building Blocks - Kaila Murni; Amelia Adhatunnisa; Berliani Tria Amanda Putri; Nyimas Muazzomi (Universitas Muhammadiyah Kuningan, 2025)
This study aims to enhance the visual-spatial intelligence of early childhood through building block play. Visual-spatial intelligence refers to the ability to understand, process, and think visually, including recognizing shapes, sizes, colors, and the capability to create and comprehend visual information in two or three dimensions. The research method employed is a literature review, analyzing relevant books and journal articles. The findings indicate that building block play stimulates children’s creativity, imagination, and logical thinking skills. This activity allows children to learn essential concepts such as shapes, sizes, patterns, and directions, significantly supporting the development of their visual-spatial abilities. Additionally, the play enhances children’s social, emotional, and collaborative skills through group interactions. Using a systematic approach involving stages such as introduction, observation, construction, creative challenges, and evaluation, building block play proves to be an enjoyable and effective educational tool for early childhood. This study recommends that educators and parents integrate building block play into daily learning activities as an effective means to support the development of visual-spatial intelligence, creativity, and critical thinking skills in young children. Appropriate support from the surrounding environment will maximize children’s learning potential, enabling them to grow and develop optimally.